G593 Team pod: a quality improvement sprint to improve pathology services. (27th April 2015) - Blackstock, S; Irvine, R; Ejiofor, F; Popa, S; Tarma, J; Furetta, A; Cleugh, F
Abstract : Whilst working as trainees in a Paediatric department, it became apparent that there were significant delays in patient pathology results. This impacted on patient care, delaying management decisions and discharges, as well as wasting clinicians' time and hospital resources. We brought this specific issue to a Quality Improvement Sprint; a 2 day hackathon, which served as a catalyst for change. Our team of doctors, managers, design students and an engineer (who subsequently became known as Team Pod) performed an onsite analysis of the process from patient bedside to pathology laboratory. The wide range of skill sets and experiences within the team were invaluable for this process. We spent time on the wards, shadowing porters, interviewed staff and using the systems in place, gaining valuable insights into the multifaceted problem. Many hindrances were highlighted. Equipment on the ward was poorly organised and sample volumes required for various investigations were unclear. Although the hospital had a pneumatic rapid delivery system (Pod System), which took minutes to deliver samples to the laboratory, it was rarely used by ward staff. Most samples were being transferred via a porter, which could take hours. A small portering team covers a vast number of clinical areas. Most pod stations had insufficient or no pods available, and there was a general notion amongst staff that the pod system was 'unreliable.' Fascinatingly, we discovered that the porters were among the highest users of the pod system. They were gathering samples, then sending them to the laboratories using the pod station in their porters' lodge. Often the porters were even unable to access the laboratories after hours so could not hand-deliver. Furthermore, many of the pods were unlabeled, so laboratory staff did not know which wards to return them to, and therefore sent them to the highest users (A&E or the Porters) perpetuating the cycle. We calculated that the overall inefficiencies in the blood sampling and transfer process was costing the trust an estimated £1.7 million per year (time spent finding equipment, waiting for porters, calling up laboratories, repeating tests, and delayed discharges). Having better identified the nature of the inefficiencies, we formulated a problem statement, and proposed distinct initiatives. This included a re-organisation of equipment on the wards, which we instigated via the ward managers. A paediatric specific reference chart with accurate blood volumes and bottles for tests has been developed. We also approached security services and ensured that all porters had appropriate access to the laboratories during and out of hours. Most significantly, we presented our findings and a business case to the trust pathology lead, and a new pod system with trackable 'chipped' pods was approved and implemented. The chipped pods are programmed to always return to their designated station. We then launched a 'pod campaign' to raise awareness of the new system within the trust. The aim was to change the culture and engage staff to realise the benefits and time saved by using the new pod system. This improvement project demonstrates how basic practices within a hospital can be improved if staff take ownership of the systems they use and engage in efforts to understand and improve processes, and change culture. It was hugely beneficial to have a team with varied experiences and perspectives, and to have dedicated time to focus on a particular issue. Following the two-day hackathon, continued significant efforts were required to see the changes delivered, but the team were motivated and enthused to make a difference. By running these events regularly within NHS trusts, it is possible to mobilise staff to initiate improvements for the care of their patients.